2020
DOI: 10.17478/jegys.635161
|View full text |Cite
|
Sign up to set email alerts
|

AGHAMIC Action Approach (A3): Its Effects on the Pupils’ Conceptual Understanding on Matter

Abstract: We are now at the onset of Fourth Industrial Revolution, thus, Education 4.0 requires more innovative and more engaging pedagogical strategies to develop globally-competitive and functionally-literate learners. Teachers must continue to innovate strategies and approaches to make Science teaching more engaging, more fun and more collaborative. This two-group quasi-experimental action research seeks to explore the effects of the developed AGHAMIC Action Approach (A 3 ) on the conceptual understanding on matter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Interest is a crucial factor in the field of science education because from the last two decades of the 20th century, this concept expanded in the field of science educational societies (Akram et al, 2017). Furthermore, science education is a quintessential component of economic progress and self-sufficiency, and an impetus for sustainable development (Rogayan, & Macanas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interest is a crucial factor in the field of science education because from the last two decades of the 20th century, this concept expanded in the field of science educational societies (Akram et al, 2017). Furthermore, science education is a quintessential component of economic progress and self-sufficiency, and an impetus for sustainable development (Rogayan, & Macanas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research showed that students taught by competent teachers consistently showed better educational outcomes (Brophy, 2001). Innovate strategies by professional teachers make science teaching more engaging, more fun, and more collaborative (Rogayan & Macanas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These are useful to the community where an individual belongs and are further useful to the nation that he lives (SEI-DOST & UP NISMED, 2011). Through the advent of technology, Science has become a potent tool in analyzing, exploring, and discovering new concepts and ideas relevant in today's generation (Macanas & Rogayan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Primary grades can acquire and exercise the most basic skills, namely: observing, classifying, inferring, measuring, predicting, and communicating -using various fun and engaging activities. Teachers must continue to innovate strategies and approaches to make science teaching more engaging, fun, and collaborative (Rogayan & Macanas, 2020).…”
Section: Introductionmentioning
confidence: 99%